Contribution of VANGL2 mutations to isolated neural tube defects - Kibar, Zoha (2010)
Vangl2 was identified as the gene defective in the Looptail mouse model for neural tube defects (NTDs). This gene forms part of the planar cell polarity pathway, also called the non-canonical Frizzled/Dishevelled pathway, which mediates the morphogenetic process of convergent extension essential for proper gastrulation and neural tube formation in vertebrates. Genetic defects in PCP signaling have strongly been associated with NTDs in mouse models. To assess the role of VANGL2 in the complex etiology of NTDs in humans, we resequenced this gene in a large multi-ethnic cohort of 673 familial and sporadic NTD patients, including 453 open spina bifida and 202 closed spinal NTD cases. Six novel rare missense mutations were identified in 7 patients, five of which were affected with closed spinal NTDs. This suggests that VANGL2 mutations may predispose to NTDs in approximately 2.5% of closed spinal NTDs (5 in 202), at a frequency that is significantly different from that of 0.4% (2 in 453) detected in open spina bifida patients (P=0.027). Our findings strongly implicate VANGL2 in the genetic causation of spinal NTDs in a subset of patients and provide additional evidence for a pathogenic role of PCP signaling in these malformations.